2015
DOI: 10.1055/s-0034-1399383
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experience with first generation HCV protease inhibitor therapy in Germany: The prospective, non-interventional PAN cohort

Abstract: The efficacy and safety of BOC- and TVR-based triple therapy in this large, "real-world" cohort were largely comparable to that reported in pivotal clinical trials, although SVR rates were lower overall. Recommended futility or treatment extension rules were violated in a substantial proportion of patients with potential implications for response, adverse events and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
4
8
1
1
Order By: Relevance
“…Basing SVR rates on clinical trials may overestimate the benefits of treatment in practice, although this issue may be of decreasing concern, as several recent studies have shown comparable efficacy between real-world and trial settings. [40][41][42][43][44] We explore the sensitivity of our results to variations in various parameter values in the online supplementary appendix; while the precise magnitudes of results vary, the overall conclusions do not: across a wide range of parameter values, model results demonstrate that increasing treatment capacity reduces the infected population and adds significant social value.…”
Section: Limitationsmentioning
confidence: 99%
“…Basing SVR rates on clinical trials may overestimate the benefits of treatment in practice, although this issue may be of decreasing concern, as several recent studies have shown comparable efficacy between real-world and trial settings. [40][41][42][43][44] We explore the sensitivity of our results to variations in various parameter values in the online supplementary appendix; while the precise magnitudes of results vary, the overall conclusions do not: across a wide range of parameter values, model results demonstrate that increasing treatment capacity reduces the infected population and adds significant social value.…”
Section: Limitationsmentioning
confidence: 99%
“…The SVR24 rate from the Irish national HCV registry compared favourably with the outcomes from other international real world studies [46, 47]. Comparing key baseline demographics and HCV characteristics between the three studies demonstrated that our cohort was younger and had a higher proportion of males.…”
Section: Discussionmentioning
confidence: 60%
“…We directly compared the SVR24 rates from our cohort with outcomes reported in the US-based HCV-TARGET study and the German-based PAN study (Fig. 5) [46, 47]. In the TPV/PR cohorts, a statistically significant difference was observed in the SVR24 rates between this study and both the HCV-TARGET and PAN studies ( p  < 0.05).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, in the German PAN cohort study [23], SVR12 rates of 55% (boceprevir) and 63% (telaprevir) were obtained in treatment-naïve patients and 51% (boceprevir) and 68% (telaprevir) in previously treated patients. The Kaiser Permanente Medical Care Program in Northern California reported SVR rates of 53% and 56% with boceprevir- and telaprevir-based triple therapy [21].…”
Section: Discussionmentioning
confidence: 99%